Dynamic Behavior and Serviceability Analysis of a New Type of U-Shaped Steel-Concrete Composite Floor Slab - Yaqin Lu; Hongkun Shang; Zhengnong Li; Kejian Ma; Lan Jiang (Advances in Civil Engineering)
A new type of U-shaped steel-concrete composite floor is analyzed in detail. The experimental test and finite element analysis of the floor are conducted to study the natural frequency and serviceability characteristics of the new composite floor structure. The natural frequency of the floor is measured under the environmental random vibration stimulating method, and the peak acceleration of the floor is measured under pedestrian-induced load. The experimental test results show that the U-shaped steel-concrete composite floor has better antiseismic behaviors and meet the specified serviceability requirements. The finite element analysis results indicate the constraints have a great impact on the calculation results. The experimental tests and FEM results of the floor are compared based on the modal assurance criterion, and the results are in good agreement. The experimental test acceleration curves demonstrate that the peak values meet the requirements of Chinese specification.